Incid?ncia, variabilidade molecular de v?rus e cultivo in vitro de meristemas de videiras cultivadas no Subm?dio do Vale do S?o Francisco - Ribeiro, Hugo Leonardo Coelho (2016)
The vine is grown in many countries, the berries being the main product with many uses, such as fresh grapes, juices and wines. The wine industry is an important economic activity in Brazil, highlighting the pole Petrolina, PE / Juazeiro, BA in sub middle of San Francisco Valley (SSFV), as the main producing region of fine table grapes in the country. The multiplication of vine cuttings is done mainly by vegetative propagation, facilitating the spread of pathogens, one of the main sources of the spread of the virus. This study aimed to evaluate the incidence of Grapevine virus A virus (GVA), Grapevine leafroll-associated virus 1 (GLRaV-1), Grapevine leafroll-associated virus 3 (GLRV-3), Grapevine fanleaf virus (GFLV) and Grapevine fleck virus (GFkV) by detecting by Double Antibody Sandwich ELISA (DAS-ELISA) in grapevines of SSFV in six municipalities located in the states of Bahia and Pernambuco, as well as analyze the regenerative capacity and in vitro development of 13 different tropical clones of vine obtained by cultivation of apical meristems and axillary buds, and finally, to analyze the variability of the fragments of the protein coat (PC) gene of the virus winding the sheet cultivars of tropical vines of the San Francisco Valley. Of the 490 samples evaluated, 320 are cultivars for table with and without seeds, 94 for wine and 76 rootstocks. Infections caused by viruses were detected in 79.4% of samples. The GLRaV-3 was the most widespread viruses, followed by GVA GFkV, GLRaV-1 and GFLV, respectively. Mixed infection was detected in 153 samples. Cultivars wine, fine table grapes and rootstocks showed total percentage of 93.2% infection, 52.6% and 31.9%, respectively. For the regenerative capacity and development in vitro, we analyzed the percentage of regeneration time and the numbers of buds, roots and leaves produced as well as the length of the internodal segments 30, 60 and 90 days of cultivation in culture medium 'MS' and 'Galzy', respectively. Of the 13 cultivars tested, four were regenerated with a percentage ranging between 7% and 47%. The occurrence of significant differences among cultivars showed different responses over time. 'Cabernet Sauvignon' presented the best regeneration response starting from apical meristem and axillary buds. 'IAC-572' stood out with the highest average height and bud and leaf numbers 30, 60 and 90. To determine the variability of the CP gene, samples of 28 BAG vines cultivars of the Embrapa Semiarid with and without of disease symptoms were analyzed by reverse transcriptase and polymerase chain reaction (RT-PCR). Of all the samples GLRaV -1, -2 and -3, zero, 10 and 19 presented infection, respectively, and eight had mixed infection. There was a high and low identity between isolates obtained from Brazilian and foreign isolated for both viruses, finding genetic divergence of the CP gene in some isolates. 13 isolates showed no significant homology with other isolates in the present study and available on GENBANK, to GLRaV-3.